Strategi Komunikasi Pemasaran Dream Coffee Cilegon dalam Meningkatkan Brand Awareness Konsumen - Ayu Anisah; Noerma Kurnia Fajarwati; Meiby Zulfikar; Achmad Nashrudin Priatna; Putri Handayani (Lembaga Pengembangan Kinerja Dosen, 2025)
The increasing number of coffee shops in the modern era, especially in developing cities such as Cilegon, has triggered increasingly competitive market conditions. Dream Coffee, as a newly established coffee shop, faces challenges in introducing its brand and attracting consumer attention amid the dominance of more established coffee shops. This study aims to examine the marketing communication strategies implemented by Dream Coffee and to identify the factors that support and hinder the process of building brand awareness among its consumers.This research employs a qualitative approach, focusing on gaining an in-depth understanding of the social phenomena occurring at Dream Coffee through descriptive data collection and direct interaction. Data were collected using structured interviews, direct observation, and documentation involving the owner, internal consultant, employees, and customers or consumers.The findings indicate that Dream Coffee utilizes various elements of Integrated Marketing Communication (IMC), including advertising, personal selling, word-of-mouth marketing, sales promotion, and events and experiences. The main supporting factors are consistent and targeted communication, internal team solidarity, and an appealing visual brand identity. Meanwhile, challenges include limited physical facilities and a market reach that has not yet been maximized. Overall, it can be concluded that Dream Coffee successfully implements effective marketing communication strategies not only digitally but also in building brand awareness and creating emotional engagement with consumers.